Religious Social Inclusion: Acculturation of The Muslim Ambengan Tradition - Wahidah, Finadatul (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
Religious conflict in Indonesia is still ongoing, and this conflict occurs because of differences in beliefs framed by mere egoism. Religious conflicts do not look at the conditions that arise in society nor the values ​​of tolerance in religion. A religiously Inclusive Society can be realized if there is social acceptance, institutions, and participation from the community. Religiously Inclusive Society built in the village of Sukoreno Umbulsari Jember cannot be separated from the acculturation process of the local culture. One of them is the ambengan tradition held by the Muslim community of Sukoreno village. This ambengan is not only attended by the Muslim community but also Christians, Catholics, and Hindus. Ambengan was carried out in the mosque, which continued with the reading of Yasin and istighosah with the interfaith community. This research has two research focuses, namely 1) How is the acculturation process of the Muslim minority Ambengan tradition in Sukoreno Village?; 2) What is the tolerance pattern for minority Muslims as a result of acculturating the ambengan tradition? This study uses a qualitative approach. The data was obtained through interviews, observation, and documentation. The data was then analyzed using qualitative data analysis methods. The study results show that 1) The acculturation process of the ambengan tradition occurs because of shared beliefs with the principle of village-harmonization. This village harmonization can also be seen in the citrus agro-industry network built by the Sukoreno village community; 2) The tolerance pattern of minority Muslims as a result of the acculturation of the ambengan tradition forms a Sufistic-ethical relationship, namely, the obedience of faith and the firmness of customs. The ambengan tradition, a tradition of the Muslim community, is attended and followed by Christians, Catholics, and Hindus to carry out the Koran and istighosah together in the mosque (Ngaji Bersama-Lintas Agama). Likewise, the traditions carried out by non-Muslim communities are also attended to and followed by the Muslim community. This research is essential as a reference for the model of interfaith tolerance that occurs in Sukoreno village. As for the novelty of this research, in addition to the model/pattern of interaction formed, there is also the principle of village harmonization (as the beginning of cultural acculturation) which can build villages independently with the citrus agro-industry network.